2021
DOI: 10.1590/s2175-97902020000419033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trichostatin A on FHIT and WWOX genes expression, cell growth inhibition and apoptosis induction in hepatocellular carcinoma WCH 17 cell line

Abstract: Previously, we evaluated the effect of trichostatin A (TSA) on the expression of DNA methyltransferase 1 (DNMT1) in Hepatocellular Carcinoma (HCC). Fragile histidine triad (FHIT) and WW domaincontaining oxidoreductase (WWOX) are two of the most common down-regulated genes in many cancers located on chromosome 3p14.2 and 16q23.3-24.1 respectively. The aim of the current study was to assess the effect of TSA on these genes expression, cell growth, and apoptosis in HCC WCH 17 cell. The cells were seeded and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In MCF7 cell, VPA was reported to induce apoptosis at the lowest dose of 0.5mM after 8 days of treatment 36 . In a similar study, Masumeh et al reported a VPA -IC50 value of 3µM 21 . Earlier reports also found morphological changes in MCF7 cells after exposure to VPA for more than 48 hrs 16 .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In MCF7 cell, VPA was reported to induce apoptosis at the lowest dose of 0.5mM after 8 days of treatment 36 . In a similar study, Masumeh et al reported a VPA -IC50 value of 3µM 21 . Earlier reports also found morphological changes in MCF7 cells after exposure to VPA for more than 48 hrs 16 .…”
Section: Resultsmentioning
confidence: 69%
“…reported a VPA -IC50 value of 3µM 21 . Earlier reports also found morphological changes in MCF7 cells after exposure to VPA for more than 48 hrs 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation